CRISPR/Cas9-mediated mutagenesis of the susceptibility gene OsHPP04 in rice confers enhanced resistance to rice root-knot nematode - Huang, Qiuling; Lin, Borong; Cao, Yuqing; Zhang, Yu; Song, Handa; Huang, Chunhui; Sun, Tianling; Long, Changwen; Liao, Jinling; Zhuo, Kan (Frontiers in Plant Science, 2023)
CRISPR crops carrying a mutation in susceptibility (S) genes provide an effective strategy for controlling plant disease, because they could be ‘transgene-free’ and commonly have more broad-spectrum and durable type of resistance. Despite their importance, CRISPR/Cas9-mediated editing of S genes for engineering resistance to plant-parasitic nematode (PPN) disease has not been reported. In this study, we employed the CRISPR/Cas9 system to specifically induce targeted mutagenesis of the S gene rice copper metallochaperone heavy metal-associated plant protein 04 (OsHPP04), and successfully obtained genetically stable homozygous rice mutants with or without transgenic elements. These mutants confer enhanced resistance to the rice root-knot nematode (Meloidogyne graminicola), a major plant pathogenic nematode in rice agriculture. Moreover, the plant immune responses triggered by flg22, including reactive oxygen species burst, defence-related genes expression and callose deposition, were enhanced in the ‘transgene-free’ homozygous mutants. Analysis of rice growth and agronomic traits of two independent mutants showed that there are no obvious differences between wild-type plants and mutants. These findings suggest that OsHPP04 may be an S gene as a negative regulator of host immunity and genetic modification of S genes through the CRISPR/Cas9 technology can be used as a powerful tool to generate PPN resistant plant varieties.